2021
DOI: 10.3390/cimb43010008
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Pineapple Rhizome Bromelain through Downregulation of the NF-B- and MAPKs-Signaling Pathways in Lipopolysaccharide (LPS)-Stimulated RAW264.7 Cells

Abstract: Bromelain is a mixture of proteolytic enzymes derived from pineapple (Ananas comosus) fruit and stem possessing several beneficial properties, particularly anti-inflammatory activity. However, the molecular mechanisms underlying the anti-inflammatory effects of bromelain are unclear. This study investigated the anti-inflammatory effects and inhibitory molecular mechanisms of crude and purified rhizome bromelains on lipopolysaccharide (LPS)-induced inflammation in RAW 264.7 macrophage cells. RAW264.7 cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 54 publications
2
12
0
1
Order By: Relevance
“…The inhibitory effects of bromelain on NF-κB and MAPK signaling pathways in this study agree with previous findings demonstrating the inhibitory effects of bromelain on the NF-κB pathway and AP-1 molecules [44,45]. Recently, the inhibitory effects of bromelain on LPS-induced NF-κB and MAPK signaling were demonstrated in RAW cells [10,46].…”
Section: Inhibitory Effects Of Bromelain Extract On Tnf-α-induced Nf-κb and Mapk Signalingsupporting
confidence: 92%
See 3 more Smart Citations
“…The inhibitory effects of bromelain on NF-κB and MAPK signaling pathways in this study agree with previous findings demonstrating the inhibitory effects of bromelain on the NF-κB pathway and AP-1 molecules [44,45]. Recently, the inhibitory effects of bromelain on LPS-induced NF-κB and MAPK signaling were demonstrated in RAW cells [10,46].…”
Section: Inhibitory Effects Of Bromelain Extract On Tnf-α-induced Nf-κb and Mapk Signalingsupporting
confidence: 92%
“…The HPLC profile revealed that the bromelain extract used in this study was identical to stem bromelain, and the peak of bromelain extract appeared at a retention time of 0.9 min. The bromelain extract examined in this study was previously characterized for protease activity, and its molecular weight was calculated as 25-27 kDa [10]. The HPLC profile (Figure 1) revealed that bromelain extract was not a pure compound, in line with the results of a previous study reporting that stem bromelain consisted of four proteases, one jacalin-like lectin, and two protease inhibitors according to LC-MS/MS [11].…”
Section: Hplc Profilesupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, finding effective and low-toxicity anti-inflammatory drugs to control inflammation is critical for the prevention or treatment of these diseases (Tang et al, 2021). Inflammation results in the production of proinflammatory cytokines and other inflammatory mediators such as tumor necrosis factor (TNF)-α, and IL-1β, and high mobility group box 1 (HMGB1) (Insuan et al, 2021). HMGB1 plays a critical role in the pathophysiology of inflammatory diseases like sepsis (Yang et al, 2021;Hur et al, 2021).…”
Section: Introductionmentioning
confidence: 99%